2020
DOI: 10.2478/fv-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Occurence and Antimicrobial Resistant Patterns of Methicillin Resistant Staphylococcus Aureus (MRSA) Among Practicing Veterinarians in Kebbi State, Nigeria

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) is an emerging zoonotic pathogen incriminated in causing multiple disease conditions in humans and livestock. Studies have shown relationships between livestock rearing and increased MRSA colonization risk among farm workers, and also suggest that livestock may serves as reservoirs of the bacteria and could also infect humans via close contact and consumption of contaminated animal products. The aim of this study was to investigate if practicing veterinarians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…The findings of the current study revealed a serious problem with the increasing antimicrobial resistance rate among the bacterial isolates from the hospitalacquired infections, comparable to the worldwide 17,18 trends. In our study, Gram-negative bacteria showed extreme resistance against co-trimoxazole.…”
Section: Discussionsupporting
confidence: 67%
“…The findings of the current study revealed a serious problem with the increasing antimicrobial resistance rate among the bacterial isolates from the hospitalacquired infections, comparable to the worldwide 17,18 trends. In our study, Gram-negative bacteria showed extreme resistance against co-trimoxazole.…”
Section: Discussionsupporting
confidence: 67%
“…The result showed a high resistance to penicillin, oxytetracycline, neomycin, erythromycin, gentamicin, and sulfonamides. Reports from A n u e y i a g u and I s i y a k u [1], J a h a n et al [16] and G a d d a f i et al [12] in agreement showed a remarkably high MRSA resistance to penicillin because it is the drug of choice in S. aureus infection. High resistance to oxytetracycline noticed in this study could be attributed to the assertion by O l a t o y e [27] who opinioned that tetracycline is commonly used as a feed additive and for prophylaxis in animal production in Nigeria.…”
Section: Discussionmentioning
confidence: 88%
“…The current study's PCR investigation indicated the presence of the mecA gene at 163 bp in 15 of the 20 isolates that were phenotypically MRSA positive. When it comes to MRSA detection and characterization, the pres-ence of the mecA gene is the gold standard [11]. According to studies, the existence of the mecA gene in animals and animal products supports this claim [12,27,37].…”
Section: Discussionmentioning
confidence: 99%
“…MRSA strains carry a diverse and transmissible genetic element designated as MRSA colonization in dogs which have been extensively studied in most parts of the world with varying prevalence rates of 0-6 % [23]. However, despite reports of the pathogen in humans [11] and the unethical use of antibiotics by veterinary quacks and animal owners, there is very little information about the presence of MRSA in dogs in Nigeria.…”
Section: Methicillin-resistant Staphylococcus Aureus (Mrsa)mentioning
confidence: 99%